2022-RA-1196-ESGO Secondary cytoreductive surgery in endometrial cancer recurrence: how to triage patients towards surgery, a multicenter study. (20th October 2022) - Vargiu, Virginia; Rosati, Andrea; Capozzi, Vito Andrea; Gioè, Alessandro; Restaino, Stefano; Distefano, Ettore; Berretta, Roberto; Scambia, Giovanni; Fanfani, Francesco; Cosentino, Francesco
Abstract : Introduction/Background: Literature evidence showed that patients with endometrial cancer (EC) recurrence benefiting from secondary cytoreductive surgery (SCS) had significantly better survival outcomes than patients not undergoing SCS, however, only a minority is considered eligible (13–38%).In this study, we retrospectively analyzed clinical-histological variables that could predict patient operability. Methodology: Multicenter, retrospective analysis including patients with EC recurrences diagnosed through radiological and/or histological examination between January-2010 and December-2021. Results: Three-hundred-thirty-one patients have been retrieved. One-hundred-eighty-six patients underwent SCS (Group-1), while 145 were addressed to other secondary treatment (chemotherapy ± radiotherapy ± palliative care) (Group-2).Patients selected for SCS were statistically younger, with lower body mass index (BMI), better Eastern Cooperative Oncology Group-Performance Status (ECOG-PS) and with less comorbidities (Group 1 vs 2: age≥75: 9.7% vs 20.0 p<0.001, BMI≥30: 30.6% vs 44.1%, p=0.016, ECOG-PS≥2: 19.8% vs 30.3%, p<0.001, Aged-Adjusted Charlson Comorbidity Index, AACCI>2: 67.7% vs 86.2%, p<0.001) (Table-1).At univariate analysis age≥75, BMI≥30, ECOG-PS≥2, AACCI>2, augmented Ca-125, evidence of multiple-site metastasis and of a mixed pathway of recurrence were statistically significant factors for a reduced probability of undergoing SCS. At multivariate analysis only ECOG-PS≥2 (OR: 0.370, p=0.024), augmented Ca-125 (OR:0.482, p=0.042), multiple-site metastasis (OR: 0.429, p=0.024) and the mixed recurrence pathway (OR: 0.111, l=0.008) confirmed to be negative predictors. Conversely, nodal recurrence-pathway showed an OR of 2.173, p=0.042 suggesting a higher chance to undergo SCS (Table-1).Complete gross resection (CGR) was achieved in the 95.7% of patients selected for surgery ( table 1 ). Conclusion: Age>75 years, ECOG-PS≥2, positive Ca-125, evidence of multiple-site relapse, and the mixed pathway of relapse are independent negative predictors of patient operability, while the nodal pathway of relapse has been shown to be a positive predictor.Considering the CGR rate obtained in the selected population, these factors could be used to build a preoperative score to correctly identify patients who may benefit from SCS.